Metabarcoding survey of meroplankton communities in the South China Sea and Philippine Sea: Shedding light on inter-basin biogeography in the West Pacific - Qihang, Li; Yuanming, Chai; Qianwen, Shao; Zaiming, Wang; Wei, Xie; Yadong, Zhou; Dong, Sun; Xiaohui, Xie; Dongsheng, Zhang (Frontiers in Marine Science, 2022)
Planktonic larvae (meroplankton) plays an important role in both benthic and pelagic ecosystems. The meroplankton study of South China Sea (SCS) and Philippine Sea (PS) may be particularly important, where they could serve as vectors for the influx of Pacific species into the East Indies Triangle (global marine biodiversity center). Here, we employed a metabarcoding method to investigate the geographical distribution pattern of meroplankton among SCS and PS. Different primers and reference databases were tested, for a better and more reliable interpretation of the current results and improvement of the method. In this study, metabarcoding was efficient for meroplankton study with high taxonomic resolution and good accuracy. COI against NCBI NT database showed the best taxonomy annotation efficiency, followed by 18S V1-V2, then 18S V4. The SILVA database showed similar performance to the NCBI NT database for the two 18S primers. The meroplankton diversity of SCS is higher than that of PS, and both communities are dominated by Polychaeta, Mollusca, Arthropoda and Echinodermata. Meroplankton geographical patterns are significantly different between the two basins, possibly due to the different distribution of their benthic adult, as well as the influence of five key environmental factors (IC, SCM, SST, SSS and DO). Our results suggest that the unidirectional Kuroshio Current intrusion may play an important role in shaping the biogeographical pattern in the west Pacific, by facilitating planktonic-larvae flowing into the northern SCS from the Pacific, on the contrary, limiting planktonic-larvae spreading out.